ANALISIS KEKRITISAN LAHAN UNTUK PERENCANAAN REHABILITASI LAHAN DAS SOLO BAGIAN HULU (Analyses of degraded land for rehabilitation planning in upper Solo Watershed) - Nining Wahyuningrum; Tyas Mutiara Basuki (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTWater erosion is one of the causes of degraded land and a decrease in land productivity. Improvement of degraded land needs to detect sources of erosion and vulnerability level of the degraded land. The research was conducted to predict the vulnerability of soil erosion and distribution of degraded land in order to support the implementation programme of Land Rehabilitation and Soil Conservation. The research was conducted in upper Solo Watershed. Soil erosion was predicted using Universal Soil Loss Equation (USLE). The analysis of Land Capability Class was undertaken to determine the suitability of current landuse with its capability. Analysis of critical land was based on the regulations of the Directorate General of Watershed Management and Social Forestry (BPDAS-PS) Nomor 4/V-SET/2013. The data used were DEM (Digital Elevation Model) Aster (30 m x 30 m), map of the Regional Physical Planning Program for Transmigration (RePPProT) scale 1: 250,000, map of forest area (1: 50,000) from BPKH (Forest Zone Determination Center), land cover map from BPKH (1: 50,000), Google Earth imagery, rainfall data from 93 rain stations and field surveys. The results show that the upper Solo Watershed is dominated by land categorized as potentially degraded (54%), followed by slightly degraded (35%), while land which is classified as degraded occupied 7% of the total watershed. The dominant land capability is categorized as Vth class and limited by soil erosion (89%). Dry land agriculture areas were found at land capability VIth and VIIth which should not utilized for agricultural activities. Implementation of agroforestry and teracing are alternatives to prevent further land degradation and to improve the current condition.Keywords: degraded; land; planning; watershed; rehabilitation ABSTRAKErosi oleh air merupakan salah satu penyebab terjadinya degradasi dan penurunan produktivitas lahan yang mengakibatkan lahan kritis. Upaya perbaikan lahan-lahan kritis perlu mendeteksi sumber-sumber penyebab erosi dan tingkat kekritisan lahan. Penelitian ini dilakukan untuk mengetahui tingkat erosi dan distribusi lahan kritis dengan tujuan agar penerapan program Rehabilitasi Lahan dan Konservasi Tanah dapat tepat sasaran dan lahan berfungsi optimal. Penelitian dilakukan di Daerah Aliran Sungai (DAS) Solo bagian hulu. Besarnya erosi tanah diprediksi dengan Universal Soil Loss Equation (USLE). Analisis KPL (Kemampuan Penggunaan Lahan) dilakukan untuk mengetahui kesesuaian penggunaan lahan dengan kemampuannya. Analisis lahan kritis didasarkan pada peraturan Ditjen Bina Pengelolaan DAS dan Perhutanan Sosial (BPDAS-PS) No.4/VSET/2013. Data yang digunakan berasal dari analisis DEM (Digital Elevation Model) Aster ukuran 30 m x 30 m, peta Regional Physical Planning Program for Transmigration (RePPProT) skala 1: 250.000, peta kawasan hutan skala 1: 50.000 dari BPKH (Balai Penetapan Kawasan Hutan), peta penutupan lahan BPKH skala 1: 50.000, Citra Google Earth, data hujan dari 93 stasiun hujan dan survey lapangan. Hasil penelitian menunjukkan bahwa DAS Solo bagian Hulu didominasi lahan yang potential kritis (54%), diikuti agak kritis (35%), dan yang kritis 7%. Kemampuan Penggunaan Lahan (KPL) yang dominan adalah kelas V dengan pembatas utama erosi (89%). Dijumpai areal tegalan pada lahan dengan KPL VI dan VII yang seharusnya tidak sesuai untuk pertanian. Upaya yang dilakukan untuk tetap mempertahankan areal yang belum kritis dan memperbaiki areal yang sudah kritis adalah penerapan agroforestri dan terasering.Kata kunci: degradasi; lahan; perencanaan; DAS; rehabilitasi